Evaluation of performance for malaria diagnosis in health facilities by five provincial reference laboratories of China - Xuan Zhang; Jingjing Jiang; Yuan Sui; Hui Yan; Jing Xia; Ying Liu; Lingcong Sun; Xiaoxiao Wang; Jutta Marfurt; Jutta Marfurt; Shenning Lu; Shizhu Li; et al. (Frontiers Media S.A., 2023)
IntroductionThe provincial malaria diagnosis reference laboratories review and assess malaria cases diagnosed in health facilities for supporting the malaria elimination efforts and preventing re-transmission of imported malaria. The study aimed to evaluate the detection capability of malaria diagnosis in China from 2014 to 2021.MethodsData on malaria cases reported in the provincial-level administrative divisions (PLADs) of Anhui, Henan, Hubei, Guangxi, and Zhejiang from 2014 to 2021 were collected and analyzed.ResultsIn total, 5,770 malaria cases were reported from 2014 to 2021, and 99.05% (5,715/5,770) were submitted to the provincial malaria diagnosis reference laboratories. The median time between malaria cases being reported and the samples being received by reference laboratories was 6 days (Interquartile range, IQR:3-12 days) from 2017 to 2021. Diagnosis of 5,680 samples in the laboratory were confirmed by provincial reference laboratories, including 3,970 cases of Plasmodium falciparum, 414 of P. vivax, 1,055 of P. ovale, 158 of P. malariae, 1 of P. knowlesi, and 82 of mixed infections. Plasmodium species of 5,141 confirmed cases were consistent with the initial diagnosis, with a species accuracy rate of 90.53% (5,141/5,679). The accuracy of P. falciparum diagnosis in health facilities was higher than that of non-falciparum species. The inconsistency between microscopy and nested polymerase chain reaction (nPCR) results of confirmatory diagnosis was mainly in malaria-positive versus malaria-negative cases, as well as in mixed versus single infection cases.ConclusionThe provincial malaria diagnosis reference laboratories have played an important role in ensuring the accuracy and reliability of Plasmodium diagnosis in health facilities. However, the results of this study imply that capacity training for the identification of Plasmodium species in health facilities is warranted.